Exploring the occurrence of team learning behaviours in project teams over time. Issue 3 (27th May 2017) - Raes, Elisabeth; Boon, Anne; Kyndt, Eva; Dochy, Filip
Abstract: The aim of this qualitative longitudinal study is to create a more in-depth picture of the emergence of team learning behaviours throughout the lifespan of temporary project teams. In order to grasp the emergence of these behaviours, three project teams were followed from the start until the end of their project during a period of three months. Three team meetings spread over time were audiotaped and coded using a coding schema set-up to identify individual verbal behaviours and transform them into team learning behaviours. During the analysis, attention was given to the differentiation in the occurrence of different types of basic and facilitating team learning behaviours and in the occurrence of topics of learning behaviour (task – process – social) over time. Overall, no time-related patterns in terms of occurrence of type and topic of basic and facilitating team learning behaviours were found over the three meetings and across the three teams. The main driver for the occurrence of different team learning behaviours could be attributed to be the scope of the meeting during which they occur.